Tingkat Kecemasan Atlet Hasics Swimming Club Dalam Mengikuti Perlombaan Renang Antar Pelajar di Surabaya Tahun 2024 - Piara Septiya Ariyanti; Pudjijuniarto Pudjijuniarto; Joesoef Roepajadi; Made Pramono (Lembaga Pengembangan Kinerja Dosen, 2024)
Competition is an event to measure the ability and performance of athletes in a sport. Many factors can affect an athlete's performance during a race including anxiety levels. The purpose of this study is to determine the level of anxiety of Hasics Swimming Club swimming athletes who will compete in events between students in Surabaya in 2024. This study used a quantitative descriptive approach through sampling. Data is obtained from the results of the questionnaire distribution and using descriptive analysis techniques, namely by calculating the average or mean. The results of this study were overall swimming athletes from Hasics Swimming Club with an average of 53% in the moderate category of anxiety. With details of 8 athletes entering moderate anxiety levels, 6 athletes high anxiety levels and 1 athletes very high anxiety levels. Calculating the statistics of this study seen in various aspects of anxiety such as motor aspects, it is known that Hasics Swimming Club swimming athletes have a moderate anxiety level category with an average score of 16.3 from the highest score of 36. The affective anxiety aspect, showing an average score of 5.6 with the highest score of 12, falls into the moderate category. The somatic aspect of anxiety showed an average score of 15 out of the highest score of 28. As well as the cognitive anxiety aspect, the average score calculation results are 6.3 out of the highest score of 12 in the moderate category anxiety level.